The Rewriting of History in Amin Maalouf's The Crusades Through Arab Eyes - Carine Bourget (Studies in 20th & 21st Century Literature, 2006)
This paper analyzes the narrative strategies that shape Maalouf's rewriting of the history of the Crusades, examines why considerations of the problems inherent to the historiographical act are relegated to the background, and how Maalouf links his text to politics contemporary to its writing. I argue that while Maalouf brilliantly deconstructs the Western image of the Crusades as a heroic time by documenting the barbarity of the Crusaders without falling into the pitfall of simply inverting the terms of the dichotomy, the agenda driving his rewriting of this historical period leads him to partially repeat what his book is supposed to undo, witness the erasure of women in a book whose goal is to unearth a neglected perspective. Moreover, I contend that while most of the book painstakingly details the power play between and among the Crusaders and the Arabs that debunks the ideology of clash of religions and civilizations, the very brief epilogue, which draws parallels between the past and contemporary Middle Eastern politics but omits to mention key events of the nineteenth and twentieth century, tends to fall back in the very essentialism that the main narrative opposes.
Keywords: narrative strategies; Maalouf; crusades. history of the crusades; Western interpretation; barbarity; Crusaders; women; neglected perspective; perspective; Arab; Arabs; Amin Maalouf; Middle Eastern politics; Middle East; past Middle Eastern politics; contemporary Middle Eastern politics; essentialism